2014
DOI: 10.3846/16484142.2014.944210
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Level of Service Criteria for Urban Off-Street Facilities in Mid-Sized Cities

Abstract: Levels Of Service (LOS) evaluation criteria for off-street pedestrian facilities are not well defined in urban Indian context; hence an in-depth research is carried out in this regard. Defining Pedestrian Level of Service (PLOS) criteria is basically a classification problem; therefore a comparative study is made using three methods of clustering i.e. Affinity Propagation (AP), Self-Organizing Map (SOM) in Artificial Neural Network (ANN) and Genetic AlgorithmFuzzy (GA-Fuzzy) clustering. Pedestrian data are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In India, [50,165] determined six ranges of pedestrian LOS for walkways by using a quantitative technique utilizing average pedestrian space, pedestrian speed, flow rate, Table 4 Pedestrian Level of Service (PLOS) on different types of facilities based on qualitative/questionnaire survey and volume to the capacity ratio as critical parameters. The pedestrian LOS was determined using affinity propagation (AP), self-organizing map (SOM) in ANN and Genetic Algorithm (GA)-Fuzzy clustering techniques based on HCM 2010 methodology.…”
Section: Walkway Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In India, [50,165] determined six ranges of pedestrian LOS for walkways by using a quantitative technique utilizing average pedestrian space, pedestrian speed, flow rate, Table 4 Pedestrian Level of Service (PLOS) on different types of facilities based on qualitative/questionnaire survey and volume to the capacity ratio as critical parameters. The pedestrian LOS was determined using affinity propagation (AP), self-organizing map (SOM) in ANN and Genetic Algorithm (GA)-Fuzzy clustering techniques based on HCM 2010 methodology.…”
Section: Walkway Facilitymentioning
confidence: 99%
“…Ten different factors were used by [162] to estimate the overall pedestrian satisfaction level for sidewalks from different land uses. A quantitative survey technique was used by [50,165,166] where they used space and flow rate in defining LOS using affinity propagation (AP) cluster algorithm technique and HCM method. In a similar study, [166] used the quantitative technique to observe factors which influenced pedestrian movement over sidewalk, wide-sidewalk and precinct; and the difference in LOS was observed for the same space and speed.…”
Section: Sidewalk Facilitymentioning
confidence: 99%
“…Implementing the concept of walkability into cities has fostered a new culture of mobility, which brings with it many benefits, such as [12,13,14,15,16,17]: -Improving the level of safety on the streets -Decreasing the environmental footprint and reducing air pollution, traffic, noise or vibrations -Improving the attractiveness of public spaces, which can be help to support local businesses and local tourism, as well as encourage investment -Decreasing spending on construction of and repairs to the road infrastructure -Improving the health of residents and prolonging their life -Balancing the transport system load -Reducing the scale of difference in the usage of means of transport The concept of a walkable city as an alternative form of urban mobility 225.…”
Section: Walkability Conceptmentioning
confidence: 99%
“…Some studies have defined the PLOS as a classification problem. For example, Sahani and Kumar (2017) used three methods of clustering, including affinity propagation, self-organizing maps in artificial neural networks and genetic algorithm-fuzzy (GA-Fuzzy) methods, to find the most suitable clustering. They found that the GA-Fuzzy is the most suitable one.…”
mentioning
confidence: 99%